2004
DOI: 10.1093/sleep/27.1.116
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Respiratory Cycle-Related EEG Changes in Children with Sleep-Disordered Breathing

Abstract: The RCREC may reflect brief but numerous microarousals that could help to explain neurobehavioral consequences of SDB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 44 publications
1
41
0
Order By: Relevance
“…11 The first demonstration of this algorithm proved the existence of respiratory cycle-related EEG changes (RCREC) and suggested in a small sample of 10 children that the new measure could help to explain sleepiness even when the rate of apneic events (the respiratory disturbance index, or RDI) does not. 12 Studies in adults showed that RCREC, at least in the sigma EEG frequency ranges, explained substantial amounts of objectively assessed daytime sleepiness, beyond that explained by combinations of the best measures derived from polysomnography. 13 Furthermore, the observations that sigma power increased on average during inspiration while delta power simultaneously decreased suggested that the RCREC do reflect inspiratory microarousals, possibly associated with the work of breathing.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
See 1 more Smart Citation
“…11 The first demonstration of this algorithm proved the existence of respiratory cycle-related EEG changes (RCREC) and suggested in a small sample of 10 children that the new measure could help to explain sleepiness even when the rate of apneic events (the respiratory disturbance index, or RDI) does not. 12 Studies in adults showed that RCREC, at least in the sigma EEG frequency ranges, explained substantial amounts of objectively assessed daytime sleepiness, beyond that explained by combinations of the best measures derived from polysomnography. 13 Furthermore, the observations that sigma power increased on average during inspiration while delta power simultaneously decreased suggested that the RCREC do reflect inspiratory microarousals, possibly associated with the work of breathing.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…Ninety-five percent of these subjects had follow-up assessments, and among subjects with follow-up, missing data for each individual measure were minimal. The pre-specified primary explanatory variables were the arousal index (arousals per hour of sleep) and delta RCREC, which had shown initial promise as a predictor of improvements in both MSLT results 12 and parent rating scales for hyperactive behavior 49 after adenotonsillectomy in children. The primary outcome variable was the behavioral hyperactivity index.…”
Section: Analysesmentioning
confidence: 99%
“…The rules will miss some whose symptoms are truly related to their sleep disorder(s), but given increasing pleas for medical economic restraint, full-court press PSG techniques should perhaps be reserved for those whose first study is thought to be false-negative or non-diagnostic. Studies remain to be done and published which confirm that scoring subcortical arousals, cyclic alternating pattern, [70][71][72][73][74] respiratory cycle-related EEG changes to identify respiratory events, [75][76][77] abnormal nocturnal regulation of cardiac autonomic function, 78 computerized analysis of submentalis muscle activity to diagnose REM sleep behavior disorder, 79 and assessment of periodicity and circadian distribution of periodic limb movements 65,66,68,[80][81][82] are warranted, valid, and alter outcomes.…”
Section: In Closingmentioning
confidence: 99%
“…Some interim results, mainly on polysomnographic methodology within this 4-year study, have been reported previously. [12][13][14][15][16] …”
Section: Introductionmentioning
confidence: 99%